DETERMINASI KUALITAS INFORMASI LAPORAN KEUANGAN PADA SKPD PEMERINTAH KOTA TANGERANG - Ade Styanengsih (2021)
This research is using quantitative study that aims to investigate the effect of the implementation of accounting information systems, the implementation of government accounting standards, and the utilization of information technology on the quality of financial statement information. The population and sample of this study were employees of the Tangerang City SKPD BPKD, amounting to 60 respondents. This study uses multiple liniear regression statistical analysis of primary data using the SPSS 28 program. Based on the results of testing all hypotheses, this study shows that partially the implementation variables of government accounting standards have a significant positive effect on the quality of financial statement information. While the variable implementation of accounting information system and the variable of the utilization of information tevhnology have no effect on the quality of financial statement information.